Pengaruh Firm Size, Gross Profit Margin dan Good Corporate Governance terhadap Income Smooting - Wida Rahmayani, Melia; Febri Sayidil Umam, Mochamad; Syaharani, Inka (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Income smoothing is a form of earnings management practiced by companies to reduce fluctuations in reported earnings, either artificially or in real terms. This study aims to provide empirical evidence regarding the influence of firm size, gross profit margin, and good corporate governance on income smoothing practices in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was used with secondary data obtained from annual financial statements. The sampling technique used was purposive sampling, resulting in a sample of 18 companies and a total of 90 observations. The data were analyzed using panel data regression with EViews 12. The results show that firm size has no significant effect on income smoothing. In contrast, gross profit margin and good corporate governance have a significant effect on income smoothing in the observed companies. Keywords: Firm Size, Gross Profit Margin, Good Corporate Governance, Income Smoothing.